A case of Good's syndrome complicated by erythema multiforme. Issue 8 (20th August 2019) - Glick, Laura R; Wilson, William Wyatt; Fletcher, Michelle
Abstract : Good's syndrome (GS) is a rare, adult-onset combined B cell and T cell immunodeficiency with an associated thymoma. These patients have an increased risk of bacterial, fungal, viral and opportunistic infections. This report describes a 75-year-old female patient who presented with a full body rash and an anterior mediastinal mass. She underwent a biopsy of her rash and mass, which revealed erythema multiforme and WHO Type A thymoma, respectively. During her hospitalisation, she was also found to have oropharyngeal candidiasis, methicillin-susceptible Staphylococcus aureus bacteraemia and herpes simplex virus type 2 (HSV-2) skin lesions. Based on the number of infections and severity of her rash, an immunocompromised state was suspected. Immunological testing revealed a B cell and T cell deficiency as well as low serum immunoglobulins. This combination of hypogammaglobulinaemia and thymoma led to a diagnosis of GS. While there have been many case reports of GS, this is the first report of the immunodeficiency presenting with erythema multiforme.